Market entry strategies for multinational corporations doing business in Nigeria : assessing the case of Honeywell Process Solutions . - Blackburn, Andrew Philip (My University, 2017)
This study identifies and investigates the market entry strategies for multinational corporations (MNC’s) doing business in Nigeria. The study through a combination of an in depth literature review and semi structured interviews with Honeywell employees involved in the Nigerian entry, assesses the market entry of Honeywell Process Solutions and evaluates their entry into Nigeria, why they decided to enter Nigeria, what factors the company considered in the formulation of their strategy and the successful outcomes that were experienced as well as the challenges faced and the key learning’s that resulted from these challenges. Research on market entry of MNC’s into Nigeria is one of the discussion points for many international business leaders. Based on the literature MNC’s can enter into the Nigerian marketplace in the following ways; Exporting, Turnkey projects, Licensing, Franchising, Joint Ventures or Wholly owned subsidiaries. With the main entry modes defined the findings suggest that when adopting a Joint Venture (JV) strategy and in depth due diligence needs to be completed before appointing a JV partner. Before any JV agreement is executed and agreed there are significant matters that need to be addressed in order to avoid common mistakes associated with setting up and executing a JV strategy. Whilst Honeywell did ample due diligence on the potential JV partners, the focus was more compliance focussed on the points of anti-bribery and corruption. The company should have in conjunction with the compliance focus, paid more attention to the core capabilities of the partner as well as the initial setting out of the JV agreement. The JV partnership was executed without having clear roles, responsibilities and expectations defined. As a result of this, today Honeywell Process Solutions finds itself in a difficult position to move forward and grow the business in Nigeria.
MBA Thesis
Keywords: Conglomerate corporations -- South Africa,Joint ventures -- South Africa,International business enterprises -- Nigeria.